The Heart of Our Music: Underpinning Our Thinking : Reflections on Music and Liturgy by Members of the Liturgical Composers Forum - Foley, John B., 1939- (Book collections on Project MUSE., 2015)
N The Heart of Our Music, master practitioners of the art of liturgical music come together to offer enriching insights, a stirring vision, and practical new ideas that will change the way you think about liturgy and liturgical ministry. These reflections are written with the needs of parish liturgists and liturgical musicians in mind.